Literature Review: A Comparative Analysis of Postoperative Urinary Tract Infection Risk between Long-Term and Short-Term Catheterization - Nurfaisah Fadilah; Aziz Beru Gani; Hasan Hasan (Journal La Medihealtico, 2026)
The insertion of a urinary catheter is a routine procedure in various surgical interventions to keep the bladder empty; however, prolonged catheterization is known to increase the risk of urinary tract infection (UTI) through biofilm formation, bacterial colonization, and enhanced antimicrobial resistance. This study aims to compare postoperative UTI risk between short-term and long-term catheterization to determine the safest optimal duration. The research method uses a narrative literature review of nationally and internationally indexed journals published between 2015 and 2025, using keywords related to CAUTI, short-term catheterization, long-term catheterization, and catheter duration. Analysis of 25 cohort studies showed that long-term catheter use (>7 days) results in a significantly higher incidence of CAUTI (26.7% vs 7.1%) with a relative risk of 3.84, with infection onset rising sharply from day 3 and reaching a plateau after day 14, as well as a predominance of multidrug-resistant pathogens such as Pseudomonas aeruginosa and Enterococcus faecalis. The pathogenesis involves mature biofilm formation by days 7–10, increased expression of resistance genes, and enhanced horizontal gene transfer. These findings confirm that catheter duration is the strongest independent risk factor for CAUTI, and strategies such as early catheter removal, nurse-driven removal protocols, antimicrobial-coated catheters, and closed drainage systems have been shown to reduce CAUTI incidence by 40–60%. In conclusion, short-term catheterization is significantly safer than long-term use, and implementing protocols to reduce catheter duration is the most effective measure in preventing postoperative CAUTI.